Studi Timbulan Komposisi Dan Karakteristik Sampah Domestik Kecamatan Tampan Kota Pekanbaru - Jaspi, Khalika; Yenie, Elvi; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Design of solid waste management in an area needs some basic information comprising solid waste generation data, its composition and characterictics. This research aimed to analyzed the generation, composition and characteristic of domestic waste in Tampan. Research methodology refered to SNI 19-3964-1994 based on income levels. Results showed the average domestic solid waste generation in Tampan was 1.45 litre/person/day or 0.19 kg/person/day. Domestic waste composition Tampan was dominated by organic waste about 93,60%, composed by mostly 50 % food waste, and anorganik waste about 6,40%, composed by mostly 3,77 % mirror waste. For physical characteristic, domestic waste density was 0.13 kg/litre with compaction factor of 0,97. Chemical characteristic including water content was 31,37 %, volatile content was 55,62 % and ash content was 11,35 %.Keywords: Domestic Waste, Solid Waste Generation, Waste Composition, Waste Characteristic